ACSM's introduction to exercise science - Potteiger, Jeffrey Aaron 1958- (Wolters Kluwer, 2024)
"ACSM's Introduction to Exercise Science provides an overview of the components important to developing a solid foundation and appreciation of all aspects of exercise science. This book is designed for first-year students in exercise science or any of the related areas, including athletic training and sports medicine, clinical and sport biomechanics, clinical exercise physiology, exercise and sport nutrition, exercise physiology, exercise and sport psychology, and motor development, control, and learning. The 13 chapter topics and content were chosen to represent both the foundational and the broad-based professional areas and issues of exercise science"--